Design management : managing design strategy, process, and implementation - Best, Kathryn, ....- (London : Fairchild Books, 2015)
All designers will feel that creativity and innovation are at the heart of their designs. But for a design to have an effective and lasting impact it needs to work within certain structures, or have those structures created suitably around it. No matter how you work, a design can always be improved by assessing where it fits into the market, how it best to strengthen it before it's set in stone, who it could appeal to. It needs to be managed. In this accessible and informative second edition, Kathryn Best brings together the theory and practice of design management. With new interviews, case studies and related exercises, she provides an up to date guide for students wanting to know more about the strategy, process and implementation crucial to the management of design. The book takes its reader through the essential steps to good management of design and highlights topics currently under debate. In each part of the book Strategy, Process and Implementation are each explained using advice from leaders in the industry and real life examples. Best breaks up each part into clear and readable sections to create the perfect undergraduate book on design management.
Includes bibliographical references and index.
Keywords: Industrial design -- Management